2016
DOI: 10.1016/j.exer.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Lens regeneration from the cornea requires suppression of Wnt/β-catenin signaling

Abstract: The frog, Xenopus laevis, possesses a high capacity to regenerate various larval tissues, including the lens, which is capable of complete regeneration from the cornea epithelium. However, the molecular signaling mechanisms of cornea-lens regeneration are not fully understood. Previous work has implicated the involvement of the Wnt signaling pathway, but molecular studies have been very limited. Iris-derived lens regeneration in the newt (Wolffian lens regeneration) has shown a necessity for active Wnt signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
(112 reference statements)
1
13
0
Order By: Relevance
“…Functional studies by Hamilton et al have shown that Wnt/β-catenin signalling needs to be supressed for successful lens regeneration to occur via the cornea-lens route. 116 When the Wnt pathway was held in a state of active signalling, there was a reduction in cases of successful lens regeneration in Xenopus. Conversely, when Wnt signalling was supressed, there was no reduction in regenerative ability.…”
Section: Wolffian Lens Regenerationmentioning
confidence: 99%
“…Functional studies by Hamilton et al have shown that Wnt/β-catenin signalling needs to be supressed for successful lens regeneration to occur via the cornea-lens route. 116 When the Wnt pathway was held in a state of active signalling, there was a reduction in cases of successful lens regeneration in Xenopus. Conversely, when Wnt signalling was supressed, there was no reduction in regenerative ability.…”
Section: Wolffian Lens Regenerationmentioning
confidence: 99%
“…These findings add to a growing base of knowledge showing various forms of lens regeneration employ different signaling mechanisms and evolved independently (e.g. retinoic acid and Wnt signaling; Hamilton et al, 2016;Thomas & Henry 2014).…”
Section: Fgf1 Strongly Induces Lens Formation In Cultured Corneasmentioning
confidence: 57%
“…Sperm nuclei for transgenesis were prepared as previously described (Sive et al, 2000). Transgenic larvae were generated using a protocol similar to the REMI method with slight modifications noted (Kroll et al, 1996;Hamilton et al, 2016). Sperm nuclei were incubated with linearized DNA without egg extract, as described in (Sparrow et al, 2000).…”
Section: Generation Of Transgenic Xenopus Laevismentioning
confidence: 99%
“…Differences between any two groups were not statistically significant as measured by Fisher’s Exact Test (Fisher, 1922). The observed regenerative rates were higher than what Filoni et al (1997) observed; however, our experiments were carried out in an ex vivo culture system where the cornea is tucked directly into the optic cup so that it is in close contact with the neural retina, typically leading to high rates of regeneration (Fukui and Henry, 2011; Hamilton et al, 2016; Thomas and Henry, 2014). Figure 2I, shows a portion of mature cornea collected from the dorsal limbal region of a post-metamorphic froglet, tucked inside of a larval eyecup.…”
mentioning
confidence: 67%
“…Larval host eyes were lentectomized and to ensure that any observed regeneration was derived from the donor tissue and not the cornea epithelium of the larval host, cornea epithelia were completely removed from larval eyes (including the point of attachment to the underlying cornea endothelium). Transplant fragments were then collected and immediately placed into the larval eyecups in an ex vivo eye culture system (see Fukui and Henry, 2011; Hamilton et al, 2016; Thomas and Henry, 2014). These eyes were then removed from the animals, and placed into culture media consisting of: 61% L-15 powder (Invitrogen, Carlsbad, CA); 100 U/ml of penicillin and 100 µg/ml of streptomycin (Mediatech, Manassas, VA); 10% fetal bovine serum (Invitrogen, Carlsbad, CA); 2.5 µg /ml of Amphotericin B (Sigma, St. Louis, IL); and 4 µg /ml of Marbofloxacin (Sigma, St. Louis, IL).…”
mentioning
confidence: 99%